Characterization of layered silicate dispersion in polymer nanocomposites using Fourier transform infrared spectroscopy - Zhang, Xingui (2013)
Fourier transform infrared (FTIR) spectroscopy was used to characterize the state of dispersion of layered silicate in polymer nanocomposites. The nanocomposite samples were based on poly(hexamethylene isophthalamide) and montmorillonite nanoclay prepared by melt intercalation. The infrared spectra of Si[BOND]O stretching bands between 1150 and 960 cm−1 are found to be very sensitive to the extent of nanoclay dispersion at the molecular level. Increased level of nanoclay delamination resulted in significant changes to the out-of-plane amath image mode at 1082 cm−1 and the two in-plane modes bmath image and bmath image at 1050 and 1030 cm−1, respectively. The amath image mode shows a substantial increase in intensity and shifts toward lower wave numbers. The bandwidths of the bmath image and bmath image modes are reduced significantly. The bmath image mode also shifts toward higher wave numbers in exfoliated nanoclay. Hence, FTIR can complement other methods to characterize the morphology of polymer nanocomposites.